A Framework to Delineate Precipitation‐Runoff Regimes: Precipitation Versus Snowpack in the Western United States. Issue 22 (28th November 2019) - Chen, Xiaodong; Duan, Zhuoran; Leung, L. Ruby; Wigmosta, Mark
Abstract: Snowpack accumulation/ablation affects the runoff response to precipitation by modulating the water flux reaching the surface. Previous studies mostly focused on "rain‐on‐snow" events. Here we propose a framework to extend the scope and classify precipitation events accompanied by snow accumulation/ablation (precipitation‐and‐snow, or PAS, events) into five regimes. This framework is applied to a regional climate simulation over the western United States for 1981–2015 to reveal regions where daily changes in snowpack alter the surface hydrologic responses to precipitation. Over the western United States, PAS events account for 50–90% of all the precipitation events. Compared to the broad spatial distribution of snow accumulation‐type PAS events, snowmelting‐type PAS events are limited to coastal high‐elevation areas. Atmospheric rivers, a key driver of heavy precipitation in the region, account for only 2% of the PAS events, but they trigger significant snowmelt, accounting for 20% and 11% of light and heavy snowmelting events, respectively. Key Points: Precipitation events involving snowpack are classified into five regimes based on the relative contributions of snowpack and precipitation to runoff About 40–80% of such events feature snow accumulation, but snowmelting during precipitation is nonnegligible in the Pacific Northwest Only 2% of these events are associated with atmospheric rivers, but they contribute to over 17% of snowmelting during all these events